RATE OF POSTERIOR CAPSULAR RENT AS A COMPLICATION OF RESIDENT PERFORMED CATARACT EXTRACTION PROCEDURES - Amin, Ayesha; Ayub, Tahira; Samuel, Sarah (Journal of Ayub Medical College Abbottabad, 2015)
Background: Cataract extraction is the most commonly offered treatment for cataract. This is done surgically by a number of methods which include extracapsular cataract extraction and phacoemulsification. This study was done to assess the rate of posterior capsule rupture as a complication of resident performed cataract extraction procedures. Methods: It is a descriptive case series conducted from 1st March to 1st April 2014 at Al Shifa Trust Eye Hospital, a tertiary care hospital. Cataract extraction procedures were done by first to fourth year residents. The surgical procedures done were extracapsular cataract extraction, phacoemulsification and lens matter aspiration. Results: A total of 577 cases were operated, 307 males and 270 females. Out of which 336 were right eyes and 241 left eyes. The patients were in the age range 17-80 years. Only 61 out of 577 cases had posterior capsular rent. In phacoemulsification rate of posterior capsular rent was 29% and in extracapsular cataract extraction 69%. According to the year of residency cases done by first year were 24, second year 131, third year 231 and fourth year 191 with posterior capsular rents in 3, 23, 5 and 30 cases respectively. A total of 11 cases were left aphakic, 10 after extracapsular cataract extraction and 1 after phacoemulsification. Conclusion: There is a relatively high rate of posterior capsular rupture in cataract extraction procedures performed by residents. This rate is directly related to the procedure, being low for phacoemulsification and high for extracapsular cataract extraction. Rate of posterior capsular rupture is also directly related to the skill and expertise of the surgeon, being high for second year residents as compared to third and fourth year residents. Keywords: posterior capsular rupture, phacoemulsification, extracapsular cataract extraction, cataract extraction procedures, residents